Evaluation of the attitudes of dental students about interprofessional learning using the RIPLS questionnaire - Saber Mohammadi; Sara Pourshahidi; Mohammad javad Kharazifard; Kimia HafeziMotlagh; Arghavan Tonkaboni (BMC Medical Education)
Abstract Objectives This study aimed to assess the attitude of Iranian dental students towards interprofessional education (IPE). Materials and methods This cross-sectional study was conducted on a diverse group of 235 third-, fourth—, fifth–, and sixth-year dental students from Tehran University of Medical Sciences in 2020–2021. The Readiness for Interprofessional Learning Scale (RIPES) was used for data collection. The content validity of the questionnaire was confirmed by an expert panel (n = 4) and the content validity ratio (CVR) calculation. Its face validity was evaluated by administering it to 26 dental students and calculating CVR. The effects of demographic variables (gender, marital status, academic year, previous history of filling out the questionnaire, and participation in IPE courses) on the attitude of students were analyzed by a linear regression model. The final score of students was then calculated. Results Demographic variables had a significant effect on the total score (P < 0.05), and females, singles, and senior students acquired a higher score. The mean score was also significantly higher in those with previous experience filling out a similar questionnaire and participating in IPE courses (P < 0.05). The mean score of students’ readiness for IPE was 70.19 ± 14.29%, and the mean acquired score of 88.1% was higher than the optimal threshold of 60. Conclusion The study’s findings underscore the positive attitude of dental students towards IPE, providing strong support for including and implementing this educational model in the dental curriculum.